Exploring the recognition and restoration of land rights for the San communities in South Africa : a legal comparative perspective with respect to Australia and Canada - Bester, Carla (Stellenbosch : Stellenbosch University, 2025)
Thesis (LLM)--Stellenbosch University, 2025.